2020
DOI: 10.1021/acs.nanolett.0c03414
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy via Targeting Cancer Stem Cells Using Vaccine Nanodiscs

Abstract: Cancer stem cells (CSCs) proliferate extensively and drive tumor metastasis and recurrence. CSCs have been identified in over 20 cancer types to date, but it remains unknown how to target and eliminate CSCs in vivo. Aldehyde dehydrogenase (ALDH) is a marker that has been used extensively for isolating CSCs. Here we present a novel approach to target and reduce the frequency of ALDH high CSCs by vaccination against ALDH. We have identified ALDH1-A1 and ALDH1-A3 epitopes from CSCs and developed synthetic high-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…In addition, it has been shown that crosstalk between immune cells and ALDH+ tumor cells is reciprocal, as the targeting of tumor-associated myeloid cells by the inhibition of colony-stimulating factor 1 receptor (CSF1R) resulted in the depletion of the ALDH+ CSC population in pancreatic ductal adenocarcinoma (PDAC) tumors [214][215][216]. The development of the anti-ALDH vaccines and their clinical testing in combination with immune checkpoint inhibitors can be an efficient strategy to eradicate CSC populations and improve the tumor therapy response [206][207][208].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that crosstalk between immune cells and ALDH+ tumor cells is reciprocal, as the targeting of tumor-associated myeloid cells by the inhibition of colony-stimulating factor 1 receptor (CSF1R) resulted in the depletion of the ALDH+ CSC population in pancreatic ductal adenocarcinoma (PDAC) tumors [214][215][216]. The development of the anti-ALDH vaccines and their clinical testing in combination with immune checkpoint inhibitors can be an efficient strategy to eradicate CSC populations and improve the tumor therapy response [206][207][208].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the dendritic cell (DC)-based vaccines demonstrated that the DC pulsed by the cell lysates of ALDH + CSCs inhibited primary and metastatic tumor growth in the vaccinated xenograft tumor models. As for now, the CSC–DC vaccines were successfully tested for several tumor entities, including melanoma, head and neck squamous cell carcinoma (HNSCC), and breast cancer [ 206 , 207 , 208 ]. Thus, targeting CSCs with these vaccines alone or in combination with immune checkpoint inhibitors may lead to new avenues for anticancer immunotherapy.…”
Section: Aldh-targeted Therapies For Pca Patientsmentioning
confidence: 99%
“…Although ongoing clinical trials are still evaluating its potential benefits in BC [ 218 ], this example serves as an illustration of the possibilities of such strategies. Additionally, immunotherapy is emerging as a promising tool to manipulate the TME and target BCSCs, directly or indirectly [ 115 , 219 , 220 , 221 , 222 , 223 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from TAAs and neoantigens, cancer stem cells (CSCs) and other non-neoplastic compartments may serve as potential targets for gliomas. Nanodiscs delivering CSC-derived ALDH1-A1 and -A3 peptides have been shown to induce potent anti-tumor activity and prolong animal survival in multiple mouse models ( Hassani Najafabadi et al, 2020 ). Overall, sHDL nanodisc serves as a versatile platform with potent anti-tumor efficacy.…”
Section: Immunotherapy In Gliomamentioning
confidence: 99%